THE IDENTIFICATION OF TYPES OF FIGURATIVE LANGUAGE FOUND IN OBJECT DESCRIPTIONS IN BULELENG REGENCY TOURISM OFFICE WEBSITE - Clareza Savitri; Made Aryawan Adijaya Adijaya; Made Suardana Suardana (Lingua Scientia, 2026)
This study aims to identify the types of figurative language used in the object descriptions published on the official website of the Buleleng Regency Tourism Office (Visit North Bali). Figurative language plays a significant role in tourism promotion, as it enhances aesthetic appeal, fosters emotional engagement, and strengthens persuasive communication. This research employed a descriptive design using content analysis. The data were collected from 36 tourism object descriptions in the “Amazing Place” category on the website. The analysis was conducted based on Abarms and Harpham’s (2005) theory of figurative language. The findings reveal that 90 instances of figurative language were identified. The most dominant types are personification (39%) and imagery (34%), followed by hyperbole (7%), metaphor (6%), symbolism (6%), onomatopoeia (4%), idiom (3%), and simile (1%). The results indicate that figurative language significantly enhances the promotional appeal of tourism destinations by creating vivid imagery and fostering emotional connections with readers. This study highlights the importance of expressive linguistic strategies in strengthening digital tourism promotion.